Characterization and kinetics study of activated coconut shells, cow bones and zeolite based adsorbent for pome treatment - Abdulrahman Oyekanmi, Adeleke (2018)
Palm oil mill effluent (POME) is a high strength agro-allied wastewater containing both organic pollutants and heavy metals. The discharge of POME into the environment without adequate treatment contributes to diseases affecting humans and aquatic lives. However, there is the necessity to reduce the pollutants to a very low level of discharge to reduce the impact of the toxic effect of the pollutants on the environment and the aquatic population. The conventional approach for the treatment of POME is expensive compared to the method of adsorption. The method of adsorption has shown to be cost and time effective for research. Thus, the objective of this study was to prepare composite adsorbent from activated coconut shell carbon (ACSC), activated cow bone powder (ACBP) and zeolite for the treatment of POME using the optimum particle size obtained in a batch adsorption study. The characterization of the ACSC, ACBP and zeolite was obtained using pendant drop contact angle experiment. The result illustrated that the contact angles of the ACSC, ACBP and zeolite respectively were 105.20ᵒ, 95.70ᵒ and 25. 20ᵒ. The result of the contact angles showed that activated coconut shell carbon and activated cow bone powder were hydrophobic materials while the zeolite was hydrophilic. The investigation of the chemical composition of the materials using energy dispersive x-ray (EDX) indicated that the major elements of both ACSC and ACBP were predominantly C, Ca2+ and O and Si for zeolite and C, Si, O, Na, Mg, Ca and P as the major elements on the surface of the composite while the XRF showed that the composite contained CaO and SiO2 as the major compounds. The point of zero charge (pHpzc ) of 5.28 achieved showed that the composite contained acidic surface which influenced cationic exchange in the supernatant and the surface of the composite. The CEC after adsorption was observed as 0.8918±0.0669 meq/g. The optimal batch adsorption of COD and NH3-N was obtained at under fixed condition of pH 7, 105 minutes contact time at 150 rpm shaking speed and 150 μm particle size for ACSC, ACBP and zeolite. The prepared composite adsorbent contained functional groups of CH, C=C, C-O-C, OH using the Fourier transform irradiation (FT-IR) analysis. The optimal operation parameters of the adsorption process for the reduction of COD and NH3-N using the central composite design (RSM) was recorded at pH 10, 50 rpm of shaking speed for 2 h and by using 3 mm of composite particle size and 125 gL-1 of the adsorbent at initial concentration of POME of 1 ml per 500 ml volumetric flask. The results revealed that the investigated factors evidently induced the reduction of the parameters. The experimental data of COD, NH3-N, Cd, Fe and Pb from the batch study were fitted to the isotherm and kinetic models. The result of the isotherm study fitted best to the Langmuir equation model for COD, NH3-N, Fe and Cd which indicated that the adsorption of the pollutants from the supernatant was favourable on a mono layer surface. The Frendlich isotherm fitted experimental data better than the Langmuir and the Temkin isotherm for Pb which showed that the adsorption process was effective on a heterogeneous surface. The investigation showed that the uptakes of COD, NH3-N, Cd, Fe and Pb from the experimental data were fitted to the pseudo-second order kinetic model which implied that the process of adsorption was by chemisorption. Furthermore, the fixed bed packed composite adsorption was conducted and the experimental data were fitted to Thomas and Adams-Bohart model. The model parameters were obtained from the breakthrough curves, the effective adsorption of COD was obtained at lower flow rate influent concentration. Desorption of the spent adsorbent was suitably conducted using 0.5M NaOH and breakthrough was obtained at longer retention time. It can be concluded that a mesoporous and granular composite adsorbent was effective for the treatment of both organic and heavy metal pollutants. It was observed that both batch isotherm and kinetic study can be effectively applied for the treatment of POME using the composite adsorbent, although the effectiveness of the batch adsorption study showed to be more suitable than the fixed bed continuous column for the removal of pollutants of POME. However, due to the potential of the composite adsorbent for the treatment of POME, the treatment efficiency of the adsorbent has shown that the composite have the potential to be used for the treatment of pollutants of high strength wastewater.